Sustainability Preferences Under Stress: Evidence from COVID-19 - Döttling, Robin; Kim, Sehoon (Journal of Financial and Quantitative Analysis, 2024)
Abstract We document fragile demand for socially responsible investments (SRIs) by retail mutual fund investors. Using COVID-19 as an economic shock, we show funds with higher sustainability ratings experienced sharper declines in retail flows during the pandemic, controlling for fund characteristics. The decline in retail SRI fund flows is sharper than that of institutional flows, more pronounced when economies are hit harder by COVID-19, and unlikely to be driven by fund performance, past flows and size, or shifting investor attention. Corroborated by out-of-sample survey evidence, our findings highlight the high sensitivity of SRI demand by retail investors with respect to income shocks.